Indigenous subsistence economy in central-northern Mendoza (Argentina) - García, Alejandro (Revista Chilena de Antropología, 2017)
Progress in the study of etnohistorical Huarpes (after 1551 A.D.) and prehispanic societies of central-northern Mendoza has involved various proposals on their subsistence economy. The lack of overall assessment of the information on the subject has created a situation of uncertainty and doubt. This article aims to help clarify the issue through the analysis of all available data and the discussion of its main aspects. As a result the presence of numerous assumptions with little or no empirical support is observed, and it is proposed that subsistence in the analyzed area included the development (though not necessarily by all groups) of activities in agriculture, hunting, fishing, gathering and grazing. The important consumption of agricultural products, and the lack of evidence that fishing activity played a fundamental role in diet at the regional level, is also highlighted.